ACCORDANCE OF THE QUALITY OF 250 GRAM IVORY CARTON PACKING BASED ON INDONESIAN NATIONAL STANDARD (SNI) DUPLEX CARTON - Lala Hucadinota Ainul Amri; Efnyta Muchtar; Inez Zahra Pradipta (Kreator, 2020)
Ivory paperboard is a type of cardboard consisting of 2 or more layers and is commonly used for primary packaging. The formulation of the research problem is how the process of testing the properties of 250-gram ivory paperboard and the results of testing the properties of ivory paperboard based on the Indonesian National Standard (SNI) for duplex cardboard. The purpose of this study was to determine the quality of the physical properties, opacities, and chemical properties of 250-gram ivory paperboard and to determine the suitability of the paperboard that was tested with the Indonesian National Standard (SNI) for duplex cardboard. The research method used in this research is the quantitative method and testing method based on Indonesian National Standard (SNI) 0123: 2008 Duplex Carton. Based on test data obtained by ivory paperboard 250 grams, gramatur 247,573 gr / m2, mass density 766,479 kg / m3, pull resistance (picking) in good condition, oil penetration 7,852, water absorption 29.54 gr / m2, properties folds on MD (not broken), CD (broken), degree of whiteness (brightness) 82.52%, sheet composition on the top layer (chemical layer), the water content of 5.22%. So from the income, 250-gram ivory paperboard is in accordance with the Indonesian National Standard (SNI) 0123: 2008 Duplex cardboard.Keywords— Ivory paperboard, Print quality properties, Indonesian National Standard 0123:2008 Duplex Carton.